Penerapan Pertanggungjawaban Pidana Korporasi Dalam Tindak Pidana Penggelapan Dana Pihak Ketiga Di Perbankan - Yevendri Yevendri (Normative Jurnal Ilmiah Hukum, 2026)
In an effort to collect funds, banks must recognize the sources of funds that exist in various levels of society in different forms. One of them is third party funds. These funds must be managed well, because they are temporary and must be returned, meaning that the bank as the holder of third party funds must be responsible for the safety of these third party funds. However, incident after incident has befallen the existence of these third party funds, one of which is the occurrence of a criminal act of embezzlement of third party funds committed by the defendant with the initials HAW, an employee of the BRI Watampone Branch, who was examined and tried by the Watampone District Court in Watampone, in Decision Number 387 / Pid.B / 2012 / PN.Wtp. which stated that the defendant with the initials HAW was guilty of committing the crime of "Embezzlement in His Position or Work" as regulated in Article 374 of the Criminal Code. The declaration of the defendant, identified as HAW, as the perpetrator of the crime of embezzlement of third-party funds and the sentence of four years' imprisonment minus the time served in detention, is inseparable from the acceptance of corporations as subjects of criminal law, which has brought about significant changes in the definition of criminal actors and raised issues regarding corporate criminal liability. In declaring the defendant, identified as HAW, as the perpetrator of the crime of embezzlement of third-party funds and sentencing him to four years' imprisonment minus the time served in detention, the system and theory of corporate criminal liability were applied, with management as the responsible creator and administrator, supported by identification theory and functional actor theory.